Cystic fibrosis, with a focus on new therapies for causal treatment - CFTR protein modulators - Klara Iwaniszyn-Zapołoch; Anna Małek; Magdalena Marzęda; Olga Wysokińska; Karolina Zadrożna; Mateusz Fabiś; Bartłomiej Wójcik (Kazimierz Wielki University, 2022)
INTRODUCTION: Cystic fibrosis is a severe, multi-system involvement genetic disease. It is estimated that 1 in 2,500 people are affected, most commonly Europeans.  It used to lead to death in childhood, but patients now live to adulthood. STATE OF KNOWLEDGE: Thanks to screening tests carried out in many countries, the disease can be detected quickly at birth and treatment can be implemented as soon as possible. Following the discovery of the CF transmembrane conductance regulator gene (CFTR), in which the mutation responsible for cystic fibrosis occurs, a great deal of research has been done to discover the best pathway for causal treatment. A new group of drugs called modulators, which improve the function of the CFTR protein, was developed. These preparations have been approved for clinical use by the US Food and Drug Administration (FDA) and the European Medicines Agency (EMA). Approximately 85-90% of patients are eligible for treatment, based on the mutations they have. Importantly, from the beginning of 2022, the aforementioned causative therapies will appear on the Polish list of reimbursed drugs. SUMMARY: Thanks to genetics and biology, it was possible to discover modulators of the CFTR protein. With a quick diagnosis and the fastest possible initiation of targeted treatment, patients have a chance for a longer and better life. Today, the median age to which people with CF live is 46.2 years. It is said that these innovative therapies can not only alleviate the course of this incurable disease, but also prevent the occurrence of severe complications. Unfortunately, we do not know the far-reaching effects of the preparations, so at the moment we can only hope for as many studies as possible showing the effects of their use.